The Effect of Ferulic Acid on Inflammation in a Myocardial Ischemia-Reperfusion Experimental Model: The Effect of Ferulic Acid on Inflammation - Ahmed, Naseer; Qazi, Ayesha Ihsan; Mehmood, Mazhar; Tanveer, Meera; Kiran, Romaisa; Shabir, Mohsin (Pakistan Journal of Health Sciences, 2025)
Cardiovascular disease is a leading cause of death globally, with ischemia-reperfusion injury (IRI) causing tissue damage through oxidative stress and inflammation. Interleukin-6 (IL-6) plays a role in IRI-related myocardial damage. Ferulic acid, a plant-derived phenolic compound, shows potential as an anti-inflammatory and antioxidant therapy to reduce IRI. Objectives: To investigate the dose-dependent protective effect of ferulic acid in an experimental myocardial ischemia-reperfusion injury model, focusing on its impact on serum IL-6 levels. Methods: This experimental study was conducted over 6 months by the Department of Pharmacology at Rehman College of Dentistry, Peshawar, Pakistan, utilizing healthy male Sprague Dawley rats weighing 300–350 grams (g). Rats showing signs of illness were excluded from the study. Twenty rats were randomly allocated to control (n=10) and treatment (n=10) groups. Preceding the induction of ischemia-reperfusion injury, the treatment group was administered oral ferulic acid for 15 days; controls were untreated. Data were analyzed using SPSS version 23.0. Results are presented as mean ± standard deviation, and the mean difference was compared by an independent sample t-test, taking<0.05. Results: IL-6 levels in serum were measured using ELISA, with control rats showing higher IL-6 (66–80 ng/l) than ferulic acid-treated rats (46–55 ng/l). There was a significant reduction in IL-6 levels in the treated group. This indicates ferulic acid lowers inflammation in myocardial ischemia-reperfusion injury. Conclusions: It was concluded that the ability to lower the IL-6 level and modulate oxidative-inflammatory pathways, ferulic acid can be a promising therapeutic agent to attenuate myocardial inflammatory responses and reperfusion injury.